Pertanggungjawaban Pidana terhadap Tindak Pidana Pencurian dalam Putusan 361/Pid.B/2025/PN Jmb - Emir Adzan Syazali; Nurdin Salomo Pasaribu; Dodi Satriyo; Senta Fito Pratama; Albi Ternando; M. Arya Putra Pangestu (Universitas Batanghari Jambi, 2026)
Criminal liability is central to assessing whether a person can be sanctioned for their actions. The theft case in Jambi District Court Decision Number 361/Pid.B/2025/PN Jmb illustrates the practical application of this principle, where defendant Heru Prasetyo was found guilty based on the objective and subjective elements of theft as stipulated in Article 362 of the Criminal Code. This research aims to examine criminal liability and the legal principles used by judges in deciding cases, adopting normative legal research methods through statutory and conceptual approaches, as well as examining court doctrine and jurisprudence. The results show that judges consider fault, intent, capacity to be responsible, the purpose of punishment, and the protection of the victim's rights. This decision also reflects an effort to balance substantive justice and the interests of society, so that criminal law functions as an instrument for law enforcement, restoring victims' rights, and creating a sense of security in community life.